PEREMPUAN DALAM PEMBANGUNAN BERWAWASAN GENDER : SEBUAH KAJIAN DALAM PERSPEKTIF FENOMENOLOGIS - MARIA KATJE TUPAMAHU, (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
The limitations of women in accessing economic resources have an impact on the performance and role of women in nation building. The 'gender-minded development' program is a strategic alternative to make it easier for women to access everything related to women's empowerment and quality of life. The method used is qualitative approach method with observation and interview. The results showed that gender-minded development in ambon city has not been maximally implemented and realized because there are still strategic positions dominated by men so that women's access to economic potentials and policy making is still very limited.